Approach to the professional identity of rural and multigrade teachers in the state of Chiapas, Mexico (Revista Innova Educación, 2025)
This study aims to present relevant aspects of the construction of the professional identity of rural and multigrade teachers in the state of Chiapas. The research was conducted using a qualitative approach, with the objective of understanding the experiences of three primary school teachers working in rural and multigrade schools, each with more than ten years of service. Narrative interviews were used, allowing for the recovery of meaningful experiences related to being a teacher in these contexts. The data were analyzed using Atlas.ti software and organized into four categories: the family and its influence on career choice; entry into the profession and first workplace; the relationship with rural life and educational actors; and teaching practice in rural and multigrade classrooms. Among the findings, it stands out that professional identity begins to take shape within the family environment and is strengthened through teaching in challenging contexts, which require personal and pedagogical strategies to address student diversity and community engagement. This dynamic construction is mainly sustained through teaching practice, shaped by specific school, social, and material conditions, which demand ongoing adaptation and the development of skills often not addressed in initial teacher training but essential in rural and multigrade settings.
Keywords: multigrade teachers; rural teachers; rural schools; professional identity